(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2021)
Religious expressions in rural areas is no longer a problem with the diversity it has. The social reality in Pangedaran Village is very concerning, various problems such as the education rate is very low, knowledge support activities are very minimal, even the drugs abuse is common in the village. the social setting accompanies the da’wah activities of the taklim, which demands that the recitation can fill Islamic knowledge and religious experience and the congregation’s spiritual care. Thus, it is important to reveal the da’wah activities in the recitation in caring for the congregation’s spirituality to pacify the human ego as spiritual beings. The purpose of this study is to explain the rituals, experiences of members in carrying out the routines of the taklim assembly to care for the spirituality of the congregation. Qualitative methods and descriptive analysis were used to complete and obtain relevant research results. Utilizing observation, in-depth interviews and documentation to support the data to answer the main questions of this research. The findings of this study, explained that the activities of the taklim assembly in caring for the congregation’s spirituality were carried out by implementing dhikr, eradicating illiteracy, filling in religious knowledge, recitation rituals, reading prayers, it were done consistently.. it provide opportunities for social interaction and support the spiritual care of the congregation with social activities that form social capital so that they enter the gemeinschaft of mind group that has the same drive and motive, namely the spiritual instability of the congregation. Melihat ekspresi keagamaan di pedesaan sudah tidak menjadi persoalan dengan keberagaman yang dimilikinya. Realitas sosial di Desa Pangedaran sangat memprihatinkan, berbagai persoalan seperti angka pendidikan sangat rendah, aktivitas pendukung pengetahuan sangat minim, bahkan maraknya narkoba sudah menjadi rahasia umum di Desa tersebut. Setting sosial demikian mengiringi aktivitas dakwah majelis taklim, yang menuntut pengajian dapat mengisi pengetahuan keislaman dan pengalaman keagamaan dan perawat ruhani jemaah. Dengan demikian penting untuk mengungkap aktivitas dakwah dalam pengajian tersebut dalam merawat ruhani jemaah dapat menentramkan ego manusia sebagai makhluk spiritual dan landasan aritkel ini. Tujuan penelitian ini untuk menjelaskan ritual, pengalaman anggota dalam menjalankan rutinitas majelis taklim untuk merawat kerohanian jemaah. Metode kualitatif dan menganalisis secara deskriptif digunakan untuk menyelesaikan dan memperoleh hasil penelitian yang relevan. Memanfaatkan observasi, wawancara mendalam dan dokumentasi dalam mendukung informasi atau data akurat untuk menjawab pertanyaan utama dari penelitian ini. Hasil dan diskusi pada temuan penelitian ini, menjelaskan bahwa aktivitas majelis taklim dalam merawat ruhani jemaah dilakukan dengan pelaksanaan zikir, pengentasan buta aksara, mengisi pengetahuan keagamaan, ritual-ritual pengajian, pembacaan do’a, amalan-amalan dan selawat dilakukan secara konsisten. Rutinitas jemaah memberi peluang interaksi sosial dan mendukung perawatan ruhani jemaah dengan kegiatan sosial yang membentuk modal sosial sehingga mereka masuk ke dalam kelompok gemeinschaft of mind yang memiliki dorongan dan motif sama, yaitu ketidakstabilan spiritual atau ruhani jemaah.